Comparison of step-by-step kinematics of resisted, normal and assisted 30 m sprints in experienced sprinters - van den Tillaar, R.; Gamble, P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to compare step-by-step kinematics of resisted, normal and assisted 30m sprints in experienced sprinters. Step-by-step kinematics were measured using infrared mat and laser gun in sixteen subjects during each 30 m sprint under the respective condition. The main findings were that almost all measured kinematics were affected by resisted and assisted sprint conditions. The one exception was that step frequency did not show any marked differences between assisted sprint condition in comparison to normal sprints. It is notable that employing this approach in combination with laser gun and infrared mat over 30 m makes it straightforward to analyse step-by step kinematics under different conditions in training. This approach could provide coaches, researchers and athletes with more detailed information and monitor changes in kinematics during training.